Hydrogen gettering of titaniumpalladium/palladium nanocomposite films synthesized by cosputtering and vacuum-annealing. (25th October 2018) - Lim, Hyo-Ryoung; Eom, Nu Si A; Cho, Jeong-Ho; Cho, Hong-Baek; Choa, Yong-Ho
Abstract: Nano-engineered composite film, prepared by the combination of titanium (Ti) nanoparticles with surrounding layers of palladium (Pd), has been suggested as a high performance hydrogen (H2 ) getter. Uniform TiPd film covered by a 35-nm-thick Pd layer was deposited on a silicon wafer via cosputtering and post-vacuum-annealing. As the annealing temperature increased from 200 to 400 °C, amorphous alloy and nano-aggregates were observed, and efficient structural modulation occurred at 400 °C, where dewetting of Pd cover layer from the getter surface was observed. This led to the enhancement of the chemisorption capacity of the 400 o C-annealed sample, two-times higher than that of the 300 o C-annealed sample. Abrupt change in residual gases, which typically come from a bonding process, can be mitigated by minimizing the gas transfer distance through the dewetting of the cover layer; since Ti nanoparticles surrounded by Pd exist independently of each other in the gettering layer, external H2 gas molecules can be continuously adsorbed onto still-unreacted Ti particles by passing through the dewetted channels in the Pd cover layer. This concept demonstrates a pathway towards a useful synthetic approach for high-performance thin-film getters with high adsorption capacity, fast gettering rate and good device compatibility. Highlights: Nanostructured TiPd/Pd film was synthesized by cosputtering and post-vacuum-annealing for H2 getter. Nano-aggregates in getter film and dewetting of Pd cover layer were observed after annealing at 400 °C. H2 adsorption isotherms showed high performance chemisorption capacity of nano-engineered TiPd/Pd film. Ti nanoparticles surrounded by Pd exist independently of each other, and thus can continuously adsorb H2 .